European Banking Union: a two-stroke reality - Almeida da Silva, Vitor Carlos (2020)
This paper focuses on the study concerning the European Banking Union’s conclusion. The European Banking Union was scheduled to come into existence in 2013, but it did not become a reality until 2014 when it implemented its first pillar: The Single Supervisory Mechanism. This European project appears, after the economic and financial crisis of 2007-2008 and the sovereign debt crises of 2010, as a fundamental complement to Economic and Monetary Union, since it is one of the blocks that allows its deepening, harmonising the supervision, resolution and protection of depositors in the Euro Zone. However, the third pillar, the European Deposit Insurance Scheme, has not yet been implemented, contributing to the non completion and inefficiency of this European project in the face of a new financial crisis.This text seeks to contribute to a better understanding of the European Banking Union and its pillars. It is divided into three parts: the first part is a brief background on the motivations behind the creation of the Banking Union; the second part concerns the three pillars that constitute it; and the third and final part is a brief conclusion on the outcome of this European project.